Revisión bibliográfica sobre ensayos de métodos de transferencia de calor al suelo de in situ (2016)
The present project of degree identified processes and mechanism for the transference of heat in soil, describing a brief state of the art based on a conceptual framework of the mechanical properties of the soil with respect to the temperature increases. Three types of technology were mainly grouped into two general areas, the first in situ vitrification mechanisms and secondarily heat exchanging piles. Within the in situ vitrification mechanisms two technologies are referred to one associated with the use of electrodes to generate a melt through the joule resistance mechanism and another using plasma torch with non-transferred arc- These methods have been developed as techniques of soil remediation, however there is a potential use in soil improvement. In contrast, heat transfer pile technologies emerge as clean energy alternatives in a building climate, but there is an interaction between the soil and the temperature gradients generated that improve the load bearing capacity of the foundation...